LESSONS AND TEACHINGS OF LIFE IN THE LIVES OF SCHOLARS OF THE PAST CENTURY - Mahkamova Orzigul Rahmonovna (Western European Studies, 2024)
In this article, the deep lessons and life lessons of Uzbek scholars of the last century are covered. By studying their contributions and philosophies, we gain an understanding of the cultural, intellectual, and spiritual foundations that shaped modern Uzbekistan. This study highlights the relevance of their teachings in modern times and provides valuable perspectives on education, ethics and social development
Keywords: Uzbek scholars; 20th century; education; ethics